Effects of Wedelia Ethanol Extract on Sperm Quality and Blood Cholesterol Levels in Obese Rats - Yumna Nabilah Iffatuzzahra'; Diah Kartika Wardani; Andika Gundawa Hidayat; Ulinuha Farah Makhabati; Haris Setiawan (Jurnal Biodjati, 2024)
Obesity is a complex, multifactorial condition contributing to male infertility by increasing oxidative stress, which negatively affects reproductive hormones, sperm quality, and blood cholesterol levels. The Wedelia plant (Sphagneticola trilobata (L.) Pruski) is a natural herbaceous plant containing flavonoids and tannins, known for enhancing sperm quality and inhibiting cholesterol synthesis in the blood. This study aims to determine the potential of Wedelia in improving sperm quality and regulating blood cholesterol levels. The study used 24 male Wistar rats divided into four groups, consisting of C (no HFF, distilled water only), NC (HFF, distilled water), T1 (HFF and 100 mg/Kg BW Wedelia extract), and T2 (HFF and 200 mg/Kg BW Wedelia extract). HFF was administered from weeks 1 to 3, followed with extract treatments from weeks 3 to 5. On day 36, the rats were euthanized for blood collection using hematocrit into EDTA tubes. The rats were dissected for the epididymis, which was then incised in a 10% PBS to release sperm. Sperm motility and count were observed on glass slides, while sperm viability and morphology were analyzed with hematoxylin-eosin using an Optilab microscope (400x magnification). The observation parameters included sperm morphology, count, motility, viability, total cholesterol, LDL, and HDL levels. Data were analyzed using ANOVA with DMRT post hoc testing (p â‰¤ 0.05). The results showed that T2 exhibited an increase in sperm count, motility, viability, and morphology in HFF-induced obese rats. T1 and T2 also showed enhanced HDL cholesterol and reduced total and LDL cholesterol levels. In conclucions, a Wedelia leaf extract dose of 200 mg/kg BW optimally improves sperm quality and reduces total and LDL cholesterol levels.